Stance of Indonesian Writers in Journal Articles - Qomariana, Yana; Soethama, Lirishati (Lingual Journal of Language and Culture, 2021)
Stance refers to attitude, feelings, judgment or commitment of a speaker towards a proposition. A speaker employs certain linguistics features to express his stance including hedges, boosters, self-mentions and attitude markers. This research aims at analyzing stance of Indonesian writers in social and hard science journal articles written in English by examining the use of linguistic features employed as stance markers. The research result shows that the writers of social science articles use more stance marker compares to those of hard science articles. Indonesian writers maintain the objectivity of academic writing as there was very limited use of self-mentions in the articles. The stance markers used by Indonesian writers represent the positive, negative or neutral type of stance.